The development of Western Siberia is a state scale project of the second half of the 20th century - A. M. Brekhuntsov; V. N. Bityukov (Georesursy, 2024)
The development of Western Siberia is one of the most large-scale scientific, industrial and socio-economic projects of the country in the 20th century. The state approach, scientific substantiation, production of the necessary equipment, organization of transport and exploration work were linked into a single integrated state project. As part of the USSR Ministry of Geology, the Main Directorate for Oil and Gas Exploration was created, and on January 15, 1948, an order was signed to organize the first oil exploration expedition in Tyumen. In January 1950, the Scientific and Technical Council of the USSR Ministry of Geology adopted a master plan for the study and development of the West Siberian Plate, including the placement of 26 reference wells, regional seismic profiles and prospecting in the area of reference wells on its territory. As a result, the gas fields of the Berezovskiy region and the Shaimskoe, Megionskoe and Ust’-Balykskoe oil fields were discovered. Efficient organization of work and the state approach made it possible to discover large oil reserves in the Shirotny Ob region and unique natural gas reserves in the north of Western Siberia in a short time. In December 1963, a special resolution of the Council of Ministers of the USSR on preparation for the trial operation of deposits, on the creation of infrastructure for the development of geology and oil production, research and industrial institutes was adopted. Achievements of geologists have provided the necessary basis for the creation of the largest fuel and energy complex. It was associated with the social and economic development of the region and the country.